Pengaruh Parameter Proses Pada Pencetakan 3D Printing Terhadap Akurasi Dimensi Filamen Petg Menggunakan Metode Taguchi - Rosa, Rosalina; Subhan, Muhammad; Pristiansyah, Pristiansyah (Politeknik Manufaktur Negeri Bangka Belitung, 2024)
3D printing technology is very widely used, especially in the industrial sector. In the 3D printing process, prototyping can be made in a short time. Fused Depositon Modeling (FDM) technology is a technique used to print products using materials and products that have ideal geometric characteristics. Based on the research that has been done, the authors conducted research on 3D Printing using PETG (Polyethylene Terephthalate Glycol) filament types with process parameters namely print temperature (245°C), (250°C), (255°C), infiil overlap percentage (50%), (60%), (70%), and layer height (0.05 mm), (0.10 mm), (0.15 mm). With the Taguchi L27(35) method for printing products using 3 parameters and 3 level in response to dimensional accuracy and transparency. This study aims to determine the dimensional accuracy of 3D printing product materials with PETG (Polyethylene Terephthalate Glycol) filaments with different parameters using the Taguchi Method and to find out how much they affect printing using PETG (Polyethylene Terephthalate Glycol) filaments with 3 process parameters tested are: print temperature, infiil overlap percentage, layer height, and with three levels that affect the testing of dimensional accuracy and transparency. Based on the experiments conducted in this study, it can be conclude that the highest dimensional accuracy for diameter is printed specimens with the parameter values print temperature (245°C), infiil overlap percentage (60%) and layer heights (0,05 mm, while the highest dimensional accuracy for height is printed specimens with the parameter values print temperature (245°C), infiil overlap percentage (70%) and layer heights (0,15 mm).